The art of comics : a philosophical approach - Meskin, Aaron; Cook, Roy T., 1972- (New directions in aesthetics, 2012)
"The Art of Comics is the first-ever collection of essays published in English devoted to the philosophical topics raised by comics and graphic novels. In an area of growing philosophical interest, this volume constitutes a great leap forward in the development of this fast expanding field, and makes a powerful contribution to the philosophy of art. The first-ever anthology to address the philosophical issues raised by the art of comics. Provides an extensive and thorough introduction to the field, and to comics more generally. Responds to the increasing philosophical interest in comic art Includes a preface by the renowned comics author Warren Ellis. Many of the chapters are illustrated, and the book carries a stunning cover by the rising young comics star David Heatley "--